Non-precious bimetallic catalysts for selective dehydrogenation of an organic chemical hydride system1. Issue 65 (21st August 2015) - Al-ShaikhAli, Anaam H.; Jedidi, Abdesslem; Cavallo, Luigi; Takanabe, Kazuhiro
<x xml:space="preserve">Abstract</x> Selective dehydrogenation of methylcyclohexane to toluene has been achieved using non-precious bimetallic Ni–Zn catalysts.